Reciprocal Archival Imaginaries: The Shifting Boundaries of “Community” in Community Archives - Brilmyer, Gracen; Gabiola, Joyce; Zavala, Jimmy; Caswell, Michelle (Archivaria, 2019)
Drawing on data collected from focus groups composed of users of five different community-based archives sites in Southern California, and using Benedict Anderson’s book Imagined Communities as a conceptual foundation, this article examines community archives users’ imaginations, anxieties, and affect regarding other archival users and the shifting boundaries of their community. This article asks, How do members of marginalized groups imagine fluctuating boundaries of their community by specifically conceptualizing other archival users? Community-based archives users, through this research, demonstrate their imaginaries about how their community is defined – not only by community members but also by outside forces. Our data shows a wide range of affective responses to users’ imaginaries; some see themselves as drawing on a community history that they are a part of and solidifying the scope of their community, while others are anxious about new “members” or outsiders who narrow or expand the bounds of a community. This article proposes the term reciprocal archival imaginaries – the circular, continually entangled relationships between archival users, their imaginaries, and community-based archives. Given the unique relationships between community-based archives and users – who also hold other roles as volunteers, donors, and board members and influence archival practice – reciprocal archival imaginaries reflect the ways in which users’ imaginaries and archives inform one another. Not only do community-based archives contribute to the formation of imaginaries, but imaginaries also inform archival processes and decision-making. This research, located alongside other archival scholarship that explores community archives and affect, emphasizes the importance and influence of community imaginations on the archives that form them. RÉSUMÉ Partant des données recueillies auprès de groupes de discussion composés d’usagers de cinq différentes archives communautaires du sud de la Californie, et utilisant le livre Imagined Communities de Benedict Anderson comme base conceptuelle, cet article explore les imaginations, les craintes et l’affect des utilisateurs des archives communautaires par rapport aux autres utilisateurs de ces archives et aux frontières mouvantes de leur communauté. Cet article pose la question suivante: comment les membres de groupes marginalisés imaginent les frontières changeantes de leur communauté en se représentant les autres utilisateurs des archives? Les utilisateurs des archives communautaires, à travers cette recherche, nous font part de leurs imaginaires et de la façon dont leur communauté est définie, non seulement par les membres de cette dernière, mais également par des pressions extérieures. Nos données démontrent une large gamme de réponses affectives aux imaginaires des utilisateurs; certains se perçoivent comme puisant dans l’histoire d’une communauté dont ils font partie et consolidant les limites de leur communauté, tandis que d’autres sont inquiets de voir de nouveaux « membres » ou des étrangers élargir ou restreindre les frontières d’une communauté. Cet article propose le terme imaginaires archivistiques réciproques : la relation circulaire, continuellement entremêlée, entre les utilisateurs des archives, leurs imaginaires et les archives communautaires. Étant donné la singularité des relations entre les archives communautaires et les usagers – qui y tiennent également d’autres rôles en tant que bénévoles, donateurs, membres des conseils d’administration, et ainsi influencent les pratiques archivistiques – les imaginaires archivistiques réciproques sont un reflet de la façon dont les imaginaires des usagers et les archives se nourrissent mutuellement. Non seulement est-ce que les archives communautaires contribuent à façonner les imaginaires, mais les imaginaires nourrissent également les processus et les décisions archivistiques. Cette recherche, sise en parallèle d’autres recherches en archivistique qui se penchent sur les archives communautaires et l’affect, met l’accent sur l’importance et l’influence des imaginaires de la communauté sur les archives qui les façonnent.